Meningkatkan Inklusivitas Seni: Dampak Kecerdasan Buatan (AI) dalam Karya Seni - Adrianto, Aditya Eko; Rachma Waryanti, Dessy (UNIVERSITAS INDO GLOBAL MANDIRI, 2025)
There is growing public concern that using Artificial Intelligence (AI) may threaten human aesthetic values and creative expression, potentially undermining the preservation of local cultural heritage. However, some argue that AI integration in the arts could enhance artistic inclusivity by expanding accessibility and fostering more interactive and engaging artistic experiences. Thus, it is crucial to explore AI's application in art with a nuanced understanding and a balanced approach to safeguard the essence of inclusivity. This study examines the impact of AI integration in artistic works, particularly its implications for artistic inclusivity. Employing a qualitative phenomenological approach, data were collected through in-depth interviews with five art professionals recruited via snowball sampling. Thematic analysis was conducted using artistic inclusivity as the primary interpretive lens. The findings reveal a consensus among participants that AI's presence in art is inevitable. However, they contend that AI will not fundamentally alter the nature of art or replace human creativity. Instead, AI is perceived as a potential tool to strengthen inclusivity, particularly by enhancing accessibility. This study contributes valuable insights into AI's impact on artistic inclusivity and offers guidance for artists to leverage technology responsibly, creating inclusive, sustainable, and culturally rich artworks. The findings also prompt further discussion on the ethics of AI in art and the need to balance technological innovation with the preservation of cultural identity.